(untitled) (Research, Society and Development, 2022)
Introduction: Yerba mate has several nutritional and medicinal properties, acting as a diuretic stimulant and digestion facilitator. Therefore, the use of yerba mate is being modernized and alternatives for its use and innovation are being investigated. Among the pharmacological activities attributed to the compounds present in yerba mate extracts, the following stand out: chemopreventive activity (prevention of cellular damage caused by chronic diseases), inhibition of glycation, inhibition of oxidative stress, choleretic effect (increased bile flow) and intestinal tract propulsion, vasodilator effect and antioxidant activity. The objective of this study is to analyze the organoleptic and pharmacological characteristics of mate teas marketed in Teresina Piauí, through a physical-chemical control, and comparing the information contained on the labels with the Brazilian Pharmacopeia, a physical-chemical control was carried out, through tests moisture content, total ash, acid-insoluble ash, pH, foreign material and label analysis. Result and discussion: After performing the physical and chemical tests of the mate tea samples, the organoleptic properties showed characteristic color and smell. The results of loss on drying were satisfactory, except for samples A and D. In the tests of total ash and acid-insoluble ash, the samples showed satisfactory results for all samples. Conclusion: There is a need for greater inspection by the Health Surveillance regarding the quality, safety and effectiveness of plant products sold in supermarkets.